Chapter Il signore va alla Camera. I relevi dell'archivio della Regia Camera della Sommaria - D'ARCANGELO, POTITO (Reti Medievali E-Book, 2021)
The essay offers an analysis of the largest concentration of records concerning the feudal lord- ship in the Kingdom of Naples from the 15th to the 17th century, the serie Relevi, kept at the Ar- chivio di Stato of Naples. The Relevi were the core of the enormous mass of records hold by the Archives of the Camera della Sommaria in Naples. These files must be considered as a whole: by tracing the creation, the evolution and the integration of the archives of the most important fiscal and financial court of the reign, the paper points out the crucial links between archivistic order, government of the state and seigneural power in the Aragonese and Spanish era.